The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1249/01.mss.0000188450.82733.f0
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Uptake and Muscle Desaturation Kinetics during Intermittent Cycling

Abstract: VO2 kinetics in intermittent exercise over a range of duty-cycle durations tended to associate with blood [lactate] profiles, similarly to previous demonstrations for sustained constant-load exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 29 publications
7
50
1
1
Order By: Relevance
“…5) it is likely that the duty cycle employed in this study (1:1.5 ratio with 37-43 s work intervals at *106% P max and a recovery interval at *53% P max ) was close to a tolerable maximum. This assertion is supported by the findings of Turner et al (2006), who showed participants could adhere to a 30-min intermittent cycling bout comprising of 30-s supramaximal exercise and 60-s recovery, but maintaining the same work:recovery ratio and increasing the duration of the supramaximal interval to 60 s led to premature exercise termination, an augmented _ VO 2 response and a progressive accumulation in blood lactate.…”
Section: Discussionmentioning
confidence: 66%
“…5) it is likely that the duty cycle employed in this study (1:1.5 ratio with 37-43 s work intervals at *106% P max and a recovery interval at *53% P max ) was close to a tolerable maximum. This assertion is supported by the findings of Turner et al (2006), who showed participants could adhere to a 30-min intermittent cycling bout comprising of 30-s supramaximal exercise and 60-s recovery, but maintaining the same work:recovery ratio and increasing the duration of the supramaximal interval to 60 s led to premature exercise termination, an augmented _ VO 2 response and a progressive accumulation in blood lactate.…”
Section: Discussionmentioning
confidence: 66%
“…An explanation for such a difference between mechanical and physiological variation can be explained partly, due to a musclelung vascular transit delay pushing the rising phases of short bursts of effort into recovery phases or in this Table II. Mean + s for performance, mechanical and physiological measures sampled throughout the field trial and separated based on terrain (hill (H) and downhill (DH)) and order as depicted in case blunting the response of lower power output bouts (Hurst & Atkins, 2006;Turner et al, 2006). The effects of downhill cross country mountain biking on the dissociation between power output and HR have been attributed to increased energy demands of movements not associated with pedalling but rather negotiating the course (Gregory et al, 2007;Stapelfeldt et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Turner et al (2006) compared the physiological responses to repetitions at the same intensity (120% _ VO 2max ) and work:rest ratio (1:2), but of varying duration. They found short work intervals of 30 s or less, were tolerated for 30 min with no sign of fatigue.…”
Section: Distance Valuementioning
confidence: 99%